2019
DOI: 10.35530/it.070.01.1608
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality of museums and conservation of textiles art works. Case study: Salacea Museum House, Romania

Abstract: The present paper is analyzing the quality of the air (temperature, humidity, light, contamination with fungi) inside the Museum House from Salacea, Bihor county, and the influence of such factors on textile materials that are exposed inside it in the context of the need to protect the heritage elements and in order to diminish the risks related to human health: the inhabitants, the tourists, museographers and all those who have access to the interior. Monitoring of the temperature and humidity was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Microbiological contamination and its implications on cultural heritage frescoes were studied by Radu et al [34], Mohanu et al [35], Bucsa and Bucsa [36] and Ilies , et al [37]. Further, other relevant studies focus on the determination of fungal contamination and microclimatic problems in museums [13,[38][39][40][41], sport halls [42,43] or schools [44][45][46]. These studies have shown that among the most common fungi that can be identified in the old wooden churches on the Romanian territory are Aspergillus spp., Mucor spp., Arthrinium spp., Stachybotrys spp., Scopulariopsis spp., Penicillium spp., Absidia spp., Geotrichum spp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, construction projects that require large amounts of land have led to the destruction of historical sites, including ancient buildings and monuments. Furthermore, the increase in air pollution, caused by industrialization, can also damage artifacts, leading to their decay and eventual loss (Indrie et. al., 2019;Lidelow et.…”
Section: Impact On Physical Environmentmentioning
confidence: 99%
“…The level of pollutant concentration, the indoor microclimate, as well as the exposure time are determinants both for human health and for the interiors of heritage buildings and their exhibits [53][54][55][56]. Air pollution inside heritage buildings, as well as an inadequate indoor microclimate, can negatively affect the health of visitors and employees [52,[57][58][59][60] and can have consequences on the degree of preservation inside the building [61,62].…”
Section: Introductionmentioning
confidence: 99%